Farmers’ Adoption To Hazton Technology And Its Determining Factors In Seluma Regency - Nick Oktavelly; Ketut Sukiyono; Septri Widono (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2020)
study aims to determine the level of adoption of haztontechnology by farmers and the factors that influence it inSemidang Alas Maras Subdistrict, Seluma Regency. Thisresearch was carried out in Gunung Kembang Village and itssurroundings, which was conducted in June - July 2019. Thisstudy used a descriptive method and direct interviewedusing a questionnaire as a data collection instrument. Datacollected in this study include areas (land area), inc (income),exp (rice farming experience), cons (counseling), tech(technology), and ol (internet). The analysis tool in this studyis multinomial logistic regression with SPSS. The resultsshowed that the Tech (technology / innovation) significantlyaffected the adoption of hazton technology in SemidangAlas Maras Subdistrict, Seluma Regency. The value of thelikelihood ratio test (sig) from Tech (technology / innovation)is less than the value of ? = 0.05 and the value of ?2 count>?2 table (0.05; 2). Meanwhile, the variable Area (land area),Inc (income), Exp (Experience), Cons (counseling) and Ol(access to information) did not significantly affect theadoption of hazton technology..